2023
DOI: 10.1038/s41598-023-34053-7
|View full text |Cite
|
Sign up to set email alerts
|

Genotype–phenotype correlation of X-linked Alport syndrome observed in both genders: a multicenter study in South Korea

Abstract: The genotype–phenotype correlation of the X-linked Alport syndrome (XLAS) has been well elucidated in males, whereas it remains unclear in females. In this multicenter retrospective study, we analyzed the genotype–phenotype correlation in 216 Korean patients (male:female = 130:86) with XLAS between 2000 and 2021. The patients were divided into three groups according to their genotypes: the non-truncating group, the abnormal splicing group, and the truncating group. In male patients, approximately 60% developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
1
4
1
Order By: Relevance
“…Prior studies have suggested that nonsense/frameshift variants confer the worst prognosis, followed by splice variants, and then the mildest phenotypes for missense and in-frame deletion variants. 6,20 In our study, we did not observe this genotype-phenotype correlation. None of the 5 females with nonsense/frameshift variants (mean age 63.8 y [SD 27.0], mean eGFR 75.5 ml/min/1.73m 2 [SD 28.3]) had ESKD or even eGFR <30 ml/min/1.73m 2 .…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Prior studies have suggested that nonsense/frameshift variants confer the worst prognosis, followed by splice variants, and then the mildest phenotypes for missense and in-frame deletion variants. 6,20 In our study, we did not observe this genotype-phenotype correlation. None of the 5 females with nonsense/frameshift variants (mean age 63.8 y [SD 27.0], mean eGFR 75.5 ml/min/1.73m 2 [SD 28.3]) had ESKD or even eGFR <30 ml/min/1.73m 2 .…”
Section: Discussioncontrasting
confidence: 89%
“…Thus, glycine missense variants disrupting the collagenous domain as well as protein-truncating variants (PTVs) are likely to be deleterious. Some but not all studies suggest a worse prognosis for PTVs than missense variants [4][5][6][7][8] . One glycine missense variant, p.Gly624Asp, is adjacent to a non-collagenous region and known to have a more mild phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…The GBM may show thinning with or without lamellation. Finally, recent data indicate that there are genotype–phenotype correlations in females with XLAS [ 28 ▪ , 29 ] that are consistent with findings described above for the patients in Group 1.…”
Section: Group 2: Mild-to-moderate Alport Syndromesupporting
confidence: 87%
“…From the large European cohort of 506 female XLAS patients from 195 families and another cohort of 275 female patients from 179 families in Japan, only 12–15% developed KF before the age of 40 years, and 30–40% before the age of 60 years [ 16 , 27 ]. A more recent study of 86 female patients with XLAS from Korea estimated the median age at KF to be 50.2 (39.0–61.5) years [ 28 ▪ ]. Hearing loss occurred in 5.5–28%, usually developing by middle age.…”
Section: Group 2: Mild-to-moderate Alport Syndromementioning
confidence: 99%
“…Notably, the majority of these patients were male (85.7%), and all exhibited varying degrees of hematuria (gross or microscopic). In a recent retrospective study of Korean patients with XLAS, approximately 20% of the male patients also presented with NS accompanied by hematuria at a median onset age of 7.0 years [13].…”
Section: Discussionmentioning
confidence: 99%